2002
DOI: 10.1099/00221287-148-12-4025
|View full text |Cite
|
Sign up to set email alerts
|

Altering the expression of two chitin synthase genes differentially affects the growth and morphology of Aspergillus oryzae The GenBank accession numbers for the chsB, chsC and chsA gene sequences reported in this paper are AY029261, AF410464 and AF429307, respectively.

Abstract: In Aspergillus oryzae, one full-length chitin synthase (chsB) and fragments of two other chitin synthases (csmA and chsC) were identified. The deduced amino acid sequence of chsB was similar (87% identity) to chsB from Aspergillus nidulans, which encodes a class III chitin synthase. The sequence obtained for csmA indicated that it had high similarity to class V chitin synthases. chsB and csmA disruption strains and a strain in which chsB transcription was controlled were constructed using the nitrite reductase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 30 publications
3
22
0
Order By: Relevance
“…Elimination or reduction of the expression of chsB or csmA caused obvious defects in hyphal growth and asexual development (3,18,21,43,58). Analogous observations have also been reported in other filamentous fungi (2,23,25,31,59). Deletion mutants of chsA, chsC, or chsD exhibited no clear morphological differences from the wild-type strain (29,30,58).…”
supporting
confidence: 55%
“…Elimination or reduction of the expression of chsB or csmA caused obvious defects in hyphal growth and asexual development (3,18,21,43,58). Analogous observations have also been reported in other filamentous fungi (2,23,25,31,59). Deletion mutants of chsA, chsC, or chsD exhibited no clear morphological differences from the wild-type strain (29,30,58).…”
supporting
confidence: 55%
“…Chitin confers stability to the cell wall; therefore, it is not surprising that CHS mutants are often defective in cell morphology (Shaw et al, 1991;Borgia et al, 1996;Muller et al, 2002). We describe here that Chs5 and Chs7 are most important for the morphology of yeast-like cells, conjugation hyphae, and dikaryotic hyphae of U. maydis (Figure 10).…”
Section: U Maydis Contains Eight Chssmentioning
confidence: 82%
“…This raises doubts about specific cellular functions of individual classes of CHS. Indeed, it was reported that class III CHSs are not important in U. maydis (Gold and Kronstad, 1994) and apparently do not even exist in Phycomyces blakesleeanus (Miyazaki and Ootaki, 1997), whereas this class has crucial functions in morphogenesis in Aspergillus oryzae (Muller et al, 2002) and Aspergillus nidulans . The situation is even more complicated by the fact that CHSs of different classes cooperate to mediate conidiation and hyphal growth (Motoyama et al, 1996;Fujiwara et al, 2000) or fungal virulence (Wang et al, 2001).…”
Section: U Maydis Contains Eight Chssmentioning
confidence: 99%
“…1 and 2). Formations of intrahyphal hyphae or double-layered cell walls were observed in some deletion mutants of the class V or VI chitin synthase-encoding genes and the genes involved in the biosynthesis of the glycosylphosphatidylinositol anchor that connects proteins working for cell wall structure maintenance (4,14,25,26,32,44). In N. crassa and Aspergillus oryzae, it has been reported that new hyphae are generated from septa when Woronin body plugged a septal pore (19,27,45).…”
Section: Discussionmentioning
confidence: 99%